Resilience and Sustainability of the Mississippi River Delta as a Coupled Natural-Human System - Yi Jun Xu (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
The Mississippi River Delta is home to more than two million people and is a hub for energy, transportation, and petrochemical industry of national importance in the United States. It is also home to 40% of coastal wetlands in the contiguous United States, which provide natural habitats for hundreds of species of fish and wildlife, as well as for millions of migrating birds in North America each year. However, this delta has been losing land at a rapid speed and its existence is being seriously threatened. A number of factors have contributed to the current situation, including reduced riverine sediment supply, coastal land erosion, subsidence, and sea level rise. In an attempt to determine resilience of the Mississippi River Delta, this book collected 14 articles that present the latest assessments of the river delta in five aspects: 1) riverine processes and sediment availability, 2) sediment deposition and land creation, 3) wetland loss, saltwater intrusion and subsidence, 4) community resilience and planning, and 5) review and synthesis. This holistic approach to investigating a river delta as a coupled natural-human system can be applicable for assessing other populated and industrialized deltaic regions in the world.